Sex-specific alterations in the gut and lung microbiome of allergen-induced mice - Ekpruke, Carolyn Damilola; Alford, Rachel; Rousselle, Dustin; Babayev, Maksat; Sharma, Shikha; Parker, Erik; Davis, Kyle; Hemmerich, Christopher; Rusch, Douglas B.; Silveyra, Patricia (Frontiers in Allergy, 2024)
IntroductionRecent evidence has demonstrated that the microbiome is a driver of the underlying pathophysiological mechanisms of respiratory disease. Studies have indicated that bacterial metabolites produced in the gut and lung can impact lung inflammation and immune cell activity, affecting disease pathology. Despite asthma being a disease with marked sex differences, experimental work linking microbiomes and asthma has not considered the sex variable.MethodsTo test the hypothesis that the lung and gut microbial composition impacts allergic lung inflammation in a sex-specific manner, we evaluated lung and gut microbiome alterations in a mouse model of allergic inflammation and assessed their association with lung function and inflammation phenotypes. For this, we exposed male and female adult C57BL/6J mice intranasally to 25 µg of a house dust mite extract mix (HDM) daily, or phosphate-buffered saline (PBS) as control, for 5 weeks (n = 4–6/group). DNA from fecal pellets collected before and after the 5-week treatment, and from lung tissue collected at endpoint, was extracted using the ZymoBIOMICS®-96 MagBead DNA Kit and analyzed to determine the 16S microbiome via Targeted Metagenomic Sequencing.ResultsThe HDM treatment induced a sex-specific allergic inflammation phenotype with significantly higher neutrophilia, lymphocytosis, inflammatory gene expression, and histopathological changes in females than males following exposure to HDM, but higher airway hyperresponsiveness (AHR) in males than females. In addition, sex-specific lung gene expression and associated pathways were identified HDM mix after challenge. These changes corresponded to sex-specific alterations in the gut microbiome, where the Firmicutes to Bacteroidetes ratio (F:B) was significantly reduced in fecal samples from only male mice after HDM challenge, and alpha diversity was increased in males, but decreased in females, after 5-weeks of HDM treatment.DiscussionOverall, our findings indicate that intranasal allergen challenge triggers sex-specific changes in both gut and lung microbiomes, and induces sex-specific lung inflammation, AHR, and lung inflammatory gene expression pathways, suggesting a contribution of the lung-gut axis in allergic airway disease.